DYNAMICS OF YIELD DEVELOPMENT AND TUBER QUALITY OF EARLY-RIPENING POTATO VARIETIES IN THE FOREST-STEPPE ZONE OF TYUMEN REGION - Y. P. Loginov; A. A. Kazak; L. I. Yakubishina (Овощи России, 2016)
The data of yield and tuber quality of earlyripening potato varieties obtained during tuber-formation in the forest-steppe zone of Tyumen region are presented. It was found that cv. Vesna, cv. Severniy, and cv. Red Scarlet are differed in their pattern of tuber formation in different time of growing. The cultivars Alena, Severniy, and Karatop are characterized by high starch accumulation and good taste qualities.